Experimental Study on The Effect of Epoxy Zinc and Thinner Ratio on Platform Structure Coating Quality - Lasma, Novi Anggiat; Kristiyono, Tri Agung (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Paint serves as a coating material that provides aesthetic value, adhesive strength, and protection to surfaces from environmental corrosion. The one of critical aspect is the paint and thinner ratio, which can influence adhesive strength and the performance of protection. This experimental study investigates the effect of varying ratios of epoxy zinc paint (Avantguard 750) and thinner (08450) on adhesion strength and drying rate. Paint was mixed with thinner at 10%, 20%, 30%, 40%, and 50% of the paint's volume. Steel plates were used as test specimens, coated via spray method. Adhesion quality was assessed using the “X–Cut Test” and “Cross Cut Tape Test” based on ASTM D3359 Methods A and B and the adhesion tests showed excellent results with a rating 5, indicating no peeling. Drying quality was evaluated using the “Solvent Rub” method according to ASTM D4752-20. Dry tests also have positive results with a rating 5 within 6 to 24 hours. The findings suggest that variations in thinner concentration do not significantly affect adhesion strength or drying time.